Outcomes of COVID-19 in heart failure, LVAD, and heart transplant patients in an advanced heart failure practice - Susan George; Luke C. Cunningham; David P. Nelson; Douglas A. Horstmanshof; James W. Long; Ahmed M. El Banayosy (American Heart Journal Plus, 2022)
Background: Patients with heart failure face increased morbidity and mortality when infected with COVID-19. The objective of this study was to evaluate the outcomes of patients with Heart Failure (HF), Left Ventricular Assist Devices (LVADs), or Heart Transplants (HTx) diagnosed with COVID-19 within an advanced HF practice. Methods: Out of 2635 patients followed, 96 patients were diagnosed with COVID-19 between March 2020 and January 2021. Median hospital length of stay (LOS), requirement for mechanical ventilation (MV), and mortality rate were evaluated. Results: The distribution of COVID-19 among the 96 patients was: HF = 43 (45 %), LVAD = 16 (17 %) and HTx = 37 (38 %). Among 43 HF patients, 5 (12 %) died, 18 (42 %) required hospitalization with an LOS of 7 days, 5 (12 %) required ICU and 4 (9 %) required MV. Of the 16 LVAD patients, 2 (13 %) died, 8 (50 %) required hospitalization with an LOS of 11 days, 3 (19 %) required ICU and 3 (19 %) required MV. Among 37 HTx patients, 7 (19 %) died, 23 (62 %) required hospitalization with an LOS of 9 days, 6 (16 %) required ICU and 6 (16 %) required MV. Conclusion: This report is among the first to describe the impact of COVID-19 on a diverse advanced HF practice. It highlights the risks associated with COVID-19 faced by the HF, LVAD and HTx patients. A 90-day mortality rate of 19 % with HTx patients acquiring COVID-19 is ominous as is a mortality rate of 12 % each for HF and LVAD patients. This clinical impact should serve as a reminder of unique challenges with these populations.